Color Names in "Kreewu-latweeschu-wahzu wardnice" (Eng. "Russian-Latvian-German Dictionary") (1872) by K. Valdemārs - Anitra Roze (Acta Baltico-Slavica, 2015)
Color Names in Kreewu-latweeschu-wahzu wardnice (Eng. Russian-Latvian-German Dictionary) (1872) by K. Valdemārs